Dinâmica das frações de micronutrientes catiônicos e esgotamento de formas disponíveis de boro, cobre, ferro, manganês e zinco, em solos de Minas Gerais - Ferreira, Gilvan Barbosa (Universidade Federal de Viçosa, 2003)
Este trabalho foi realizado com o objetivo de: i) analisar as frações de Cu, Fe, Mn e Zn em amostras de solos cultivados com eucalipto, em condições naturais e após a aplicação de doses desses nutrientes aos solos; ii) verificar quais delas estão disponíveis para as plantas em algumas classes de solos de Minas Gerais; iii) avaliar o poder de suprimento dos solos (incluindo o B) e iv) estudar a dinâmica de retenção das frações dos micronutrientes catiônicos após sua aplicação. Para tanto, na primeira fase amostras superficiais de 15 solos foram caracterizadas e extraídas as frações dos micronutrientes Cu, Fe, Mn e Zn: trocável (Tro), matéria orgânica (MO), óxidos de Mn (OxMn), de Fe amorfo (OxFeA) e cristalino (OxFeC) e a fração residual (Res). Os teores disponíveis foram extraídos com Mehlich-1, Mehlich-3 e DTPA pH 7,3. Numa segunda fase, 14 amostras de diferentes solos foram incubadas por 15 dias com as doses isoladas de 0,5, 2,0, 10,0, 5,0 e 5,0 mg/dm 3 de B, Cu, Fe, Mn e Zn, respectivamente, com um tratamento sem os micronutrientes citados, e outro com todos eles juntos, sempre na presença dos demais nutrientes essenciais à planta. Em seguida, as amostras foram cultivadas com milho por três ciclos de crescimento de 30 dias e os micronutrientes analisados na parte aérea das plantas. Os tratamentos constituíram um fatorial de 14 x 7, com 3 repetições em blocos ao acaso. Após cada cultivo, fez-se a extração das formas disponíveis pelos extratores CaCl 2 5 mmol/L (para B), DTPA e Mehlich-1. Os teores totais tiveram as seguintes distribuições: para Cu: Cu-Tro(0,0%) < Cu- MO(2,4%) < Cu-OxMn(6,1%) < Cu-OxFeA(15,4%) < Cu-OxFeC(15,6%) < Cu- Res(60,4%); para Fe: Fe-Tro(0,00%) < Fe-MO(0,02%) < Fe-OxMn(0,45%) < Fe- OxFeA(5,7%) < Fe-Res(20,2%) < Fe-OxFeC(73,7%); para Mn: Mn-MO(1,6%) < Mn-OxFeA(7,9%) < Mn-Tro(12,7%) < Mn-OxMn(13,4%) < Mn-OxFeC(14,5%) < Mn-Res(49,9%); e para Zn: Zn-Tro(0,5%) < Zn-MO(0,7%) < Zn-OxFeA(2,3%) < Zn-OxMn(3,1%) < Zn-OxFeC(8,4%) < Zn-Res(84,9%). Os micronutrientes variaram sua distribuição no solo em função da textura e das classes de solo utilizadas. Os extratores foram altamente correlacionados entre si nas extrações de Cu, Mn e Zn. As frações Cu-MO, Fe-Tro, Mn-Tro e Zn-Tro explicaram a maior parte da variação dos teores nativos das formas disponíveis. Os micronutrientes aplicados se distribuíram nas frações Cu-MO, Cu-OxMn e Cu-OxFeA; Fe-Tro; Mn-Tro; Zn-Tro, Zn-MO, Zn-OxMn e Zn-Res. Os extratores discriminaram bem os tratamentos usados; apenas o CaCl 2 5 mmol/L mostrou tendência consistente de esgotamento do B com os cultivos sucessivos e somente o Cu apresentou resposta significativa em produção de matéria seca. Os extratores DTPA e Mehlich-1 se diferenciaram mais fortemente na extração do Fe. Após a aplicação dos micronutrientes, as frações Cu-MO e Cu-OxMn, Mn-Tro e Mn-OxMn, Zn-Tro e Zn-OxMn explicaram a maior parte dos teores disponíveis recuperados por DTPA e Mehlich-1. As plantas de milho extraíram o Cu das frações Cu-OxMn e Cu-MO, o Fe da fração Fe-OxFeA, o Mn das frações Mn-Tro e Mn-OxMn e o Zn da fração Zn-Tro. Os teores disponíveis de Cu, Mn e Zn tiveram um ajuste adequado com conteúdo na planta, ao contrário dos teores de Fe. O DTPA ou Mehlich-1 pode ser usado com igual eficiência apenas na estimativa dos teores disponíveis de Cu, Mn e Zn, nas condições em que esse estudo foi realizado.

The aims of this work were: i) to analyze the fractions of Cu, Fe, Mn and Zn in soil samples from eucalyptus plantations under natural conditions and after addition of these micronutrients to soil, ii) to verify what fractions are available to plants in some classes of Minas Gerais State soils, iii) to evaluate the supplying power of the soils for these micronutrients (including B), and iv) study the dynamics of cations retention after their addition to soils. On the first phase, superficial samples from 15 soils were characterized and extracted for determination of Cu, Fe, Mn and Zn in fractions: exchangeable (Ex), organic matter (OM), Mn oxides (MnOx), amorphous Fe oxides (AmFeOx), crystalline Fe oxide (CFeOx) and residual fraction (Res). Availability of Cu, Fe, Mn and Zn in the soils were determined by using DTPA pH 7.3, Mehlich-1 and Mehlich-3 extractors. On the second phase, 14 samples from different soils were incubated for 15 days after addition of single doses (0.5, 2.0, 10.0, 5.0 and 5.0 mg/dm 3 for B, Cu, Fe, Mn and Zn, respectively in five treatments), addition of one mix of all doses in one treatment and absence of all doses in one treatment. For all seven treatments the remaining essential nutrients were added xjointly with the treatments. Then, the samples were used for growing corn in three sequential growth cycles of 30 days each, with the micronutrients analysed in the plant shoots. The experimental design was a factorial 14 x 7 x 3 (14 soils, 7 treatments, 3 replications) in entirely randomized blocks. After each growth cycle, the available forms of Cu, Fe, Mn and Zn were extracted with DTPA and Mehlich-1 and B extracted with CaCl 2 5 mmol/L. Distribution of the micronutrients in the fractions was: Cu-Ex(0,0%) < Cu-OM(2,4%) < Cu-MnOx(6,1%) < Cu-AmFeOx(15,4%) < Cu-CFeOx(15,6%) < Cu-Res(60,4%) for Cu; Fe-Ex(0,00%) < Fe-OM(0,02%) < Fe- MnOx(0,45%) < Fe-AmFeOx(5,7%) < Fe-Res(20,2%) < CFeOx(73,7%) for Fe; Mn- OM(1,6%) < Mn-AmFeOx(7,9%) < Mn-Ex(12,7%)< Mn-MnOx(13,4%) < Mn- CFeOx(14,5%) < Mn-Res(49,9%) for Mn; and Zn-Ex(0,5%) < Zn-OM(0,7%) < Zn- AmFeOx(2,3%) < Zn-MnOx(3,1%) < Zn-CFeOx(8,4%) < Zn-Res(84,9%) for Zn. The distribution of micronutrients in the soil was variable due to the soil texture and the different soil classes used. The extractors were highly correlated among themselves for Cu, Mn and Zn. The Cu-OM, Fe-Ex, Mn-Ex and Zn-Ex fractions were responsible for most of the variation in the native contents of the available forms of these micronutrients in the soils. The added micronutrients were distributed in the Cu- OM, Cu-MnOx, Cu-AmFeOx; Fe-Ex; Mn-Ex; Zn-Ex, Zn-OM, Zn-MnOx e Zn-Res fractions. The extractors were able to discriminate the treatments used. Only CaCl 2 5 mmol/L showed a consistent tendency of exhaustion for B in the soil after the sequential growth cycles. Only Cu showed significant response related to dry matter yield. The extractors DTPA and Mehlich-1 showed strong difference as related to Fe extraction. After addition of the micronutrientes, the Cu-OM, Cu-MnOx, Mn-Ex, Mn- MnOx, Zn-Ex and Zn-MnOx fractions were responsible for most of the available contents recovered by DTPA and Mehlich-1. Corn plants extracted Cu from the Cu- MnOx and Cu-OM fractions; Fe from the Fe-AmFeOx fraction; Mn from the Mn-Ex and Mn-MnOx fractions; and Zn from Zn-Ex fraction. The available contents of Cu, Mn and Zn were well adjusted to contents in the plant, contrary to what happened for Fe. DTPA or Mehlich-1 may be used efficiently only for estimating availability of Cu, Mn e Zn, under the conditions used in this work.
Dynamics of cationic micronutrient fractions and exhaustion of available forms of boron, copper, iron, manganese and zinc in soils from Minas Gerais State
Keywords: Micronutrientes; Fracionamento; Extratores químicos; Química do solo; Relação solo-planta; Teores de boro; Cobre e ferro; Teores de manganês e zinco; Ciências Agrárias